Hearing, Describing, and Creating Melodies in the DAW - Groffman, Josh (POGIL Activity Clearinghouse, 2021)
This activity introduces students to hearing, describing, and creating Melodies in the DAW as part of a general education, lower-level college course. Students with familiarity with concepts of rhythm and meter, the transport controls and basic functionality of the DAW, the piano roll, and entering MIDI notes into the sequencer will, by the end of the activity, be able to define melody and step/leap; describe different melodies and contrast them in terms of contour and rhythm; describe different melodies and contrast them in terms of the variable experience each creates for the listener; and create a basic melody using the piano roll in the DAW. They will continue to develop their critical aesthetic thinking skills (evaluating what makes for variable aesthetic experience in music), as well as oral/written aesthetic communication skills. (communicating their hearing and affective experience of music). Level:UndergraduateSetting: ClassroomActivity Type: Learning CycleDiscipline: MusicCourse: Introduction to Music TechnologyKeywords: Melody, rhythm, meter, contour, DAW, aesthetic
Number: 3
Keywords: dept.mus; peer-reviewed; ⛔ No DOI found